Gills as a glutathione-dependent metabolic barrier in Pacific oysters Crassostrea gigas: Absorption, metabolism and excretion of a model electrophile - Trevisan, Rafael; Mello, Danielle F.; Delapedra, Gabriel; Silva, Danilo G. H. [UNESP]; Arl, Miriam; Danielli, Naissa M.; Metian, Marc; Almeida, Eduardo A. [UNESP]; Dafre, Alcir L. (Elsevier B.V., 2016)
The mercapturic acid pathway (MAP) is a major phase II detoxification route, comprising the conjugation of electrophilic substances to glutathione (GSH) in a reaction catalyzed by glutathione S-transferase (GST) enzymes. In mammals, GSH-conjugates are exported from cells, and the GSH-constituent amino acids (Glu/Gly) are subsequently removed by ectopeptidases. The resulting Cys-conjugates are reabsorbed and, finally, a mercapturic acid is generated through N-acetylation. This pathway, though very well characterized in mammals, is poorly studied in non-mammalian biological models, such as bivalve mollusks, which are key organisms in aquatic ecosystems, aquaculture activities and environmental studies. In the present work, the compound 1-chloro-2,4-dinitrobenzene (CDNB) was used as a model electrophile to study the MAP in Pacific oysters Crassostrea gigas. Animals were exposed to 10 NI CDNB and MAP metabolites were followed over 24 h in the seawater and in oyster tissues (gills, digestive gland and hemolymph). A rapid decay was detected for CDNB in the seawater (half-life 1.7 h), and MAP metabolites peaked in oyster tissues as soon as 15 min for the GSH-conjugate, 1 h for the Cys-conjugate, and 4 h for the final metabolite (mercapturic acid). Biokinetic modeling of the MAP supports the fast CDNB uptake and metabolism, and indicated that while gills are a key organ for absorption, initial biotransformation, and likely metabolite excretion, hemolymph is a possible milieu for metabolite transport along different tissues. CDNB-induced GSH depletion (4 h) was followed by increased GST activity (24 h) in the gills, but not in the digestive gland. Furthermore, the transcript levels of glutamate-cysteine ligase, coding for the rate limiting enzyme in GSH synthesis, and two phase II biotransformation genes (GSTpi and GSTo), presented a fast (4h) and robust (similar to 6-70 fold) increase in the gills. Waterborne exposure to electrophilic compounds affected gills, but not digestive gland, while intramuscular exposure was able to modulate biochemical parameters in both tissues. This study is the first evidence of a fully functional and interorgan MAP pathway in bivalves. Hemolymph was shown to be responsible for the metabolic interplay among tissues, and gills, acting as a powerful GSH-dependent metabolic barrier against waterborne electrophilic substances, possibly also participating in metabolite excretion into the sea water. Altogether, experimental and modeled data fully agree with the existence of a classical mechanism for phase II xenobiotic metabolism and excretion in bivalves. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Mercapturic acid pathway; Glutathione; Glutathione S-transferase; Gills; Bivalves